Association of blood lead with estradiol and sex hormone-binding globulin in 8-19-year-old children and adolescents - Pan, Kaiyu; Tu, Rongliang; Cai, Zixiu; Huang, Yingdan; Zhang, Chengyue (Frontiers in Endocrinology, 2023)
Background: Metals can interfere with hormonal functioning through indirect mechanisms and by binding at the receptor site; thus, they may be associated with hormonal changes. However, there have been few studies on the health impact of metal exposure among children and adolescents. Thus, we aimed to examine the associations of blood lead level (BLL) with estradiol (E2) and sex hormone-binding globulin (SHBG) among children and adolescents aged 8–19 years in the National Health and Nutrition Examination Survey (NHANES) database. Methods: This was a cohort study of 2188 individuals from the NHANES. BLL was taken as independent variables, E2 and SHBG as dependent variable. We conducted weighted multivariate linear regression models and smooth curve fittings to evaluate the association between them. Results: The BLL was significantly positively associated with serum SHBG level in females, especially when the LnBLL quartiles are between Q3 and Q4. There was an inverted U-shaped association between BLL and E2 with the point of inflection at 1.86 μg/L and a U-shaped association between BLL and SHBG with the point of inflection at 1.86 μg/L in female adolescents aged 16-19 years. Meanwhile, In males, there was a positive trend of correlation between BLL and E2 in the 8-11 years, and 16-19 years groups.BLL was not significantly associated with E2 and SHBG in males. Conclusions: This study found an inverted U-shaped association of BLL with E2 and a U-shaped association between BLL and SHBG in female adolescents aged 16-19 years. This indicates that adjusting blood lead exposure to mitigate the effects of lead on growth and development is important for adolescents aged 16-19 years. Controlling the BLL below 1.86 μg/L may minimize the damage to E2.